Effect of climate change on the annual energy consumption of a single family house in British Columbia - Mutasim Baba, Fuad (2018)
The Earth is already experiencing some of the effects of climate change, such as rising temperature, more frequent storms, increased precipitation, etc. This paper investigates the effect of climate change on the energy consumption of a single-family house with different energy efficiency levels, i.e. bylaw to meet current National Energy Code of Canada for Buildings (NECB), and passive house (PH) to meet the PH requirements under four climate zones in British Columbia, Canada. SRES A2, RCP 4.5 and RCP 8.5 emission scenarios are used to generate future climate for 2020, 2050, and 2080. The simulation results show that for both bylaw and PH cases, heating energy consumption will be reduced while cooling energy consumption will be increased, as a result for bylaw case, the energy consumption will be decreased for four climate zones, while for PH case, the energy consumption will be increased for zone 4 & 5 and decreased for zone 6 & 7. In climate zone 5, the building fails to meet the PH requirements during 2050. Therefore, buildings designed based on historical weather data will perform differently under the changing future climates, thus the efforts should be made to design buildings that are adaptable to climate change.